A detailed review on the phytochemical profiles and anti-diabetic mechanisms of Momordicacharantia. Issue 4 (April 2022) - Oyelere, Sunday Faith; Ajayi, Oluwatobi Hezekiah; Ayoade, Titilayo Eunice; Santana Pereira, George Bueno; Dayo Owoyemi, Bolaji Charles; Ilesanmi, Ajibola Olaoluwa; Akinyemi, Olalekan Amos
Abstract: Diabetes mellitus is the most well-known endocrine dilemma suffered by hundreds of million people globally, with an annual mortality of more than one million people. This high mortality rate highlights the need for in-depth study of anti-diabetic agents. This review explores the phytochemical contents and anti-diabetic mechanisms of M. charantia (cucurbitaceae). Studies show that M. charantia contains several phytochemicals that have hypoglycemic effects, thus, the plant may be effective in the treatment/management of diabetes mellitus. Also, the biochemical and physiological basis of M. charantia anti-diabetic actions is explained. M. charantia exhibits its anti-diabetic effects via the suppression of MAPKs and NF-κβin pancreatic cells, promoting glucose and fatty acids catabolism, stimulating fatty acids absorption, inducing insulin production, ameliorating insulin resistance, activating AMPK pathway, and inhibiting glucose metabolism enzymes (fructose-1, 6-bisphosphate and glucose-6-phosphatase). Reviewed literature was obtained from credible sources such as PubMed, Scopus, and Web of Science. Abstract : Momordica charantia, Diabetes mellitus, Anti-diabetic, Phytochemical, Cucurbitaceae, Hypoglycemic, Hyperglycemia.